La felicidad o el fin olvidado de la política moderna (2018)
Article derived from the concluded research: The bodies of exception. The main objective is to examine the conditions of possibility created by the State modern policy so that men and women can lead a good life. The theoretical-methodological perspective is taken from the philosophy of Walter Benjamin, Michel Foucault and Giorgio Agamben. The methodological procedure is montage (Benjamin, 2013 and 2015). With this, we mean the work of relating perspectives to produce a kind of critical interpretation with respect to the present. The montage is organized in two moments, one destructive and the other constructive. Among the conclusions, we can advance the following : happiness is a forgotten human end, verifying that suffering has become a silent waste for politics; something which it does not respond to.Key words: happiness, politics, State, exception, modernity.